Rebo Wekasan dalam Ranah Sosial Keagamaan di Kabupaten Tegal Jawa Tengah (Analisis terhadap Ritual Rebo Wekasan di Desa Sitanjung Lebaksiu) - Ahmad Nurozi (An-Nuha : Jurnal Kajian Islam, Pendidikan, Budaya dan Sosial, 2016)
Rebo Wekasan tradition in Tegal is still carried out. Tegal community has been widely believed that on the last Wednesday of the month of Safar, it will be a lot of disasters and calamities. So many of them, both children and adults perform various rituals to avoid disasters and calamities such as the tradition of shaving a few strands of hair and a tradition of making red and white pulp, which is then distributed to their neighbors. In addition, people also visited the hill Sitanjuang to perform the ritual starting reinforcements and ngalap blessing of the ruins are believed to be the tomb of the ancestors propagator of Islam in Java, especially in rural districts Sitanjung Lebaksiu Tegal, Central Java. The purpose of research is to find out the background to the emergence of a Rebo Wekasan culture in Sitanjung Lebaksiu village of Tegal regency, Central Java, and to determine the starting reinforcement ritual Rebo Wekasan in Sitanjung Lebaksiu village of Tegal regency, Central Java. This research is a field (field research), which is in the Sitanjung Lebaksiu hill of Tegal of Central Java with a qualitative approach and phenomenological approach to the subject of ritual Rebo Wekasan research in the Sitanjung Lebaksiu village. The sources of primary, secondary and tertiary data obtained through field and documents studies related research topic by using analysis content and research instruments are researchers themselves. The results of this study demonstrate their ignorance of local people about the background of Rebo Wekasan ritual in the Sitanjung Lebaksiu village. In addition, the ritual procession of Rebo Wekasan in the Sitanjung Lebaksiu village leads to superstition actions that could plunge the society on the behavior of shirk. The meaning Â of Rebo Wekasan in the Sitanjung Lebaksiu village also been shifted into the entertainment arena and the economic opinion